Epidemiological characteristics and genetic diversity of clinically isolated dengue vector in Khyber Pakhtunkhwa, Pakistan - Fazli Zahir; Ihteshamul Haq; Mohsina Haq; Mahrukh; Abbas Saleem Khan; Wasifa Naushad; Hala Rajab; Muhammad Fahim; Sohail Ahmad; Iqbal Munir (Elsevier, 2021)
Background: Dengue virus is the major vector of the dengue and yellow-fever viruses in Pakistan that was responsible for the sporadic epidemics of dengue fever. Method: ology: In this study, mosquitoes were collected from different parts of Swat and Peshawar and were characterized morphologically to identify different Aedes species. Results: Out of collected 138 samples, 67.4% (93/138) were found to be Aedes aegypti while 26% (36/138) were characterized as Aedes albopictus mosquitoes whereas 6.6% (9/138) of the collected samples identified as non-Aedes mosquitoes and hence excluded from the study. Using the morphological characterization key, 38.7% (36/93) were identified as male Aedes aegypti whereas the remaining 61.3% (57/93) were characterized as female mosquitoes. Genetic diversity among the collected Aedes aegypti samples were determined via the gold standard method, i.e., DNA sequencing. As the mitochondrial genome is maternally inherited through the female egg and very rarely undergoes recombination and is more diverse among species, a part of the mitochondrial gene (COI) was selected for sequencing. Based on the sequencing data, phylogenetic analysis was performed to check the possible origin of the mosquitoes. Conclusion: The current study concluded that phylogenetic analysis revealed a strong association between the sequences of Swat and Peshawar with those of Asian countries, India, suggesting the possible transmission of these vector populations from India via Lahore as the sequence from Lahore were also clustered in the same group. The sequenced fragments were clustered distantly with African and European sequences. The variations in sequences from Swat, Peshawar and Lahore can give us a good picture of the vector evolution according to the changed climatic conditions of Swat. The findings of this study can be utilized for the control of adopting dengue virus vectors.